OSTRICH-CROPGRO multi-objective optimization methodology for calibration of the growing dynamics of a second-generation transgenic soybean tolerant to high temperatures and dry growing conditions - Montero Bulacio, Enrique; Romagnoli, Martín; Otegui, María Elena; Chan, Raquel L.; Portapila, Margarita (Elsevier, 2023)
Current estimates show that the impact of climate change on agriculture will result in yield losses in major crops of 8–43%, mainly due to a combination of drought and heat. Second-generation transgenic crops are expected to mitigate these constraints. Soybean HaHB4 is a second-generation transgenic crop tolerant to high temperatures and dry growing conditions created in Argentina carrying the sunflower HaHB4 gene. Soybean HaHB4 has been approved in Argentina, the United States, Brazil, Paraguay, Canada and China.